2017
DOI: 10.1002/smll.201603718
|View full text |Cite
|
Sign up to set email alerts
|

Strengthened Synergistic Effect of Metallic MxPy (M = Co, Ni, and Cu) and Carbon Layer via Peapod‐Like Architecture for Both Hydrogen and Oxygen Evolution Reactions

Abstract: The smooth electric transmission is crucial for the high-efficient electrocatalysis. Herein, a series of peapod-like metallic M P /C (M = Co, Ni, and Cu) composites is developed as bifunctional catalysts toward hydrogen and oxygen evolution reactions. For the first time, the metallic property of Cu P is confirmed through the theoretical calculation. The in-depth composition, structural and catalytic mechanism analysis of M P /C discloses that the comparable activity and considerable durability of these catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 73 publications
2
17
0
Order By: Relevance
“…[6][7][8] However,t he high cost, scarcity,a nd unsatisfactory durability of such catalysts limit their widespreadu se and largescale deployment. [13][14][15][16][17] The largescale utilization of the above materials is significantly impeded by high price ands carcity or by their single functionality. [13][14][15][16][17] The largescale utilization of the above materials is significantly impeded by high price ands carcity or by their single functionality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] However,t he high cost, scarcity,a nd unsatisfactory durability of such catalysts limit their widespreadu se and largescale deployment. [13][14][15][16][17] The largescale utilization of the above materials is significantly impeded by high price ands carcity or by their single functionality. [13][14][15][16][17] The largescale utilization of the above materials is significantly impeded by high price ands carcity or by their single functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly,r ecent efforts have mainly focused on efficient earth-abundant materials,s uch as cobalt phosphate, perovskites, transition metal oxides, and hydroxides for OER, [9][10][11][12] andt ransition metal dichalcogenides, car-bides, phosphides, and metal alloys for HER. [13][14][15][16][17] The largescale utilization of the above materials is significantly impeded by high price ands carcity or by their single functionality. Therefore, it is tremendously desirable to design ah ighly active and highly durable bifunctional electrocatalyst from earth-abundant materials for overall water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…The outer carbon fiber in the peapod‐like structure will not only build the ideal conductive network of the charge transportation in the HER or OER, but also prevent the active nanoparticles from agglomeration and peeling off during long‐time reaction. Furthermore, it is identified that there exists strengthened synergistic effect between the active nanoparticles and carbon layer via peapod‐like architecture, leading to the superior activity and comparable stability . However, the development of catalysts with peapod‐like structure toward overall water splitting is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The C dl was measured by cyclic voltammograms (CVs) in the nonfaradaic region from 0.1 to 0.2 V vs. RHE with different scan rates (Figure S9b–f and S10b, Supporting Information). The value of C dl was estimated by plotting the difference between the anodic and cathodic current density at 0.15 V vs. RHE against the scan rate, where the linear slope was twice that of the C dl . As illustrated in Figure d, the value of C dl of Co x P@NPS‐C (14.73 mF cm −2 ) is much larger than those of other materials (whose values are 0.88, 3.26, 4.54, 5.80, and 9.74 mF cm −2 for NPS‐C, Co@NC, CoP@NC, Co 2 P@NPS‐C, and CoP@NPS‐C, respectively), revealing that the Co x P@NPS‐C catalyst owns the maximal exposure of electrochemically active sites for HER.…”
Section: Resultsmentioning
confidence: 88%